Caregivers' intentions to COVID-19 vaccination for their children in China: a cross-sectional survey - Huangyufei Feng; He Zhu; Haijun Zhang; Lingsheng Cao; Li Li; Jiaohao Wang; Yingzhe Huang; Xiaozhen Lai; Yun Lyu; Rize Jing; Jia Guo; Zundong Yin; et al. (Taylor & Francis Group, 2021)
Chinese caregivers' intentions to allow their children to be vaccinated against coronavirus disease 2019 (COVID-19) is unknown. We explored the intention rate of Chinese caregivers to allow their children to be vaccinated and examined potential influencing factors and underlying reasons for their unwillingness or hesitation. From November 30, 2020, to January 31, 2021, we conducted a cross-sectional survey of 3703 caregivers in six representative provinces in China. We assessed intention rates and correlates of caregivers' intentions to vaccinate children against COVID-19, using descriptive analyses and a multiple logistic regression analysis, respectively. In the study sample, about 84.0% of caregivers intended to get their children vaccinated for COVID-19 if the vaccine was available. In particular, 92.2% of caregivers who were willing to be vaccinated themselves for COVID-19 intended to have their children vaccinated, yet among caregivers who were unwilling (or uncertain) whether to be vaccinated, only 41.1% intended to have their children vaccinated. Older age, lower education level, and perceived safety and effectiveness of the COVID-19 vaccine were associated with increased odds of caregivers intending to have their children vaccinated. Of the six provinces included in the study, residence in a province other than Hubei increased the likelihood that caregivers would choose not to have their children vaccinated. We found a relatively high vaccination rate (84.0%) among caregivers by using a cross-sectional sample in China. Concerted efforts are needed to address caregivers' concerns about vaccine safety, especially among caregivers who do not intend to be vaccinated themselves.